Open‐label, proof‐of‐concept study of brexanolone in the treatment of severe postpartum depression. (March 2017) - Kanes, Stephen J.; Colquhoun, Helen; Doherty, James; Raines, Shane; Hoffmann, Ethan; Rubinow, David R.; Meltzer‐Brody, Samantha
Abstract: Objective: Preclinical evidence indicates that rapid changes in levels of allopregnanolone, the predominant metabolite of progesterone, confer dramatic behavioral changes and may trigger postpartum depression (PPD) in some women. Considering the pathophysiology of PPD (i.e., triggered by reproductive steroids), the need for fast‐acting, efficacious treatments and the negative consequences of untreated PPD, there is an increasing focus on developing PPD therapies. Brexanolone (USAN; formerly SAGE‐547 Injection), a proprietary injectable allopregnanolone formulation, was evaluated as a treatment for severe PPD in a proof‐of‐concept, open‐label study. Methods: Four women with severe PPD, defined as a baseline 17‐item Hamilton Rating Scale for Depression (HAMD) score of ≥20, received brexanolone, titrated to a dose reflecting third‐trimester allopregnanolone levels. After a 36‐hour maintenance infusion, tapering occurred over 12 hours. Primary outcomes were measures of safety. Secondary outcomes were assessments of efficacy, including HAMD. Results: All enrolled patients completed the study. Fourteen adverse events were reported, of which none was severe. Starting at the first measure after infusion initiation and continuing through Hour 84, mean HAMD total scores were reduced to levels consistent with remission of symptoms. All other efficacy assessments showed similar improvements. Conclusions: Brexanolone was well tolerated and demonstrated activity in severe PPD. Larger, double‐blind trials are needed for further evaluation.